The Recent Progress on Nickel@Silver Metals Core@Shell Nanoparticles Application in Printed Conductive Materials – A Mini-Review - Pajor-Świerzy A; Szczepanowicz K (Nanotechnology, Science and Applications)
Anna Pajor-Świerzy, Krzysztof Szczepanowicz Jerzy Haber Institute of Catalysis and Surface Chemistry Polish Academy of Sciences, Kraków, 30-239, PolandCorrespondence: Anna Pajor-Świerzy, Email anna.pajor-swierzy@ikifp.edu.plAbstract: This mini-review paper gives a brief summary of recent works in the development of bimetallic core@shell nanoparticles composed of nickel (as a core) and a silver shell (Ni@Ag NPs). We present the methods of Ni@Ag NPs synthesis, ink preparation, and their coatings formation. We also place emphasis on the selection and optimization of the sintering process of materials based on Ni@Ag NPs. Finally, the challenges in the application of Ni@Ag NPs in printed conductive structures are presented.Keywords: nickel@silver core@shell nanoparticles, conductive inks, sintering methods, conductive coatings, printed electronics